Model Pictorial sebagai Representasi Menyelesaikan Soal Cerita Matematis - Agus Prianto (Idealmathedu: Indonesian Digital Journal of Mathematics and Education, 2019)
This paper presents a study of the Pictorial model as a mathematical representation in solving mathematical words problem. The ability of mathematical representation is an important key for students in solving mathematical words problems and being successfull in mathematics learning. Therefore, this ability should be emphasized, developed and owned by students in learning mathematics. The Pictorial Model can be used as a first step in representing and simultaneously modeling/illustrating the purpose of a mathematical words problem. This Pictorial model approach combined with basic algebraic concepts is expected to be able to assist all students in understanding as well as solving mathematical description problems in which usually students find them difficult. In this way, students can ultimately develop their competencies and mathematical abilities optimally.